2003
DOI: 10.1002/ana.10489
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Parkinson's disease: Signals for neuronal degradation

Abstract: Despite being the subject of intense study, the pathogenesis of Parkinson's disease still remains unclear. In recent years, however, there has been increasing evidence to support a role for genetic factors in its cause. This has come from twin and family studies, the mapping and cloning of PARK genes that are associated with the development of PD, and analysis of potential susceptibility genes. There is also evidence indicating that environmental factors may play a role in the disease process. It is likely tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
227
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(239 citation statements)
references
References 102 publications
2
227
0
8
Order By: Relevance
“…Previous studies have suggested the upregulation of p53 and active caspase-3 mediating apoptosis in the degenerating dopaminerbic neurons causing PD (Tatton, 2000;Tatton et al, 2003). Consistently, our analysis reveals the upregulation of p53 and active caspase-3 (Figs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have suggested the upregulation of p53 and active caspase-3 mediating apoptosis in the degenerating dopaminerbic neurons causing PD (Tatton, 2000;Tatton et al, 2003). Consistently, our analysis reveals the upregulation of p53 and active caspase-3 (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…Apoptosis has been implicated in the pathogenesis of PD causing the degeneration of dopaminergic neurons (Mattson, 2000;Tatton, 2000;Tatton et al, 2003;Ekshyyan and Aw, 2004). Apoptosis is a programmed cell death that is mediated by a family of cysteine proteases called caspases (Sinkovics, 1991;Elmore, 2007;Ouyang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase 3 has also been implicated in cell death following a number of neurodegenerative insults including global ischaemia, 12,13 focal ischaemia, [14][15][16][17][18][19] transient ischaemia of the spinal cord, 20 neonatal cerebral hypoxia-ischaemia, [21][22][23] traumatic brain injury, [24][25][26] Alzheimer's disease, [27][28][29] Huntington's disease, [30][31][32] and Parkinson's disease. [33][34][35][36][37] It was therefore hypothesized that overexpression of caspase 3 may sensitize the animal to normal (physiological) apoptotic processes that occur during development and natural ageing and confer particular susceptibility to neurodegenerative insults. To test this hypothesis, a caspase 3 transgenic mouse line was generated using a yeast artificial chromosome (YAC) containing the human genomic DNA spanning the full-length gene including all regulatory elements.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of PD are sporadic, possibly caused by complex interactions between common genetic and environmental risk factors [1], thus making it difficult to elucidate the exact pathogenic mechanisms.…”
mentioning
confidence: 99%